2019
DOI: 10.1159/000496630
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Mammalian Target of Rapamycin May Augment the Increase in Soluble Klotho Levels in Renal Transplantation Recipients

Abstract: Background/Aims: α-Klotho is mainly expressed in the kidneys, and its soluble form can prevent vascular calcifications. Inhibition of the mammalian target of rapamycin (mTOR) upregulates Klotho. We assessed serial changes in the levels of soluble Klotho (sKlotho) in recipients before and after renal transplantation and investigated the effects of an mTOR inhibitor. Methods: Serum sKlotho levels were measured in 36 recipients before and 1 year after transplantation and compared between those taking everolimus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Eighteen of these were excluded from the full-length review as they did not report the outcome of interest, while six articles were excluded because they were not observational studies. Thus, 15 studies (10 cohort studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] with a total of 431 KTx recipients and 5 cohort studies [ 68 , 69 , 70 , 71 , 72 ] with a total of 108 living kidney donors) were included. The literature retrieval, review, and selection process are demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen of these were excluded from the full-length review as they did not report the outcome of interest, while six articles were excluded because they were not observational studies. Thus, 15 studies (10 cohort studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] with a total of 431 KTx recipients and 5 cohort studies [ 68 , 69 , 70 , 71 , 72 ] with a total of 108 living kidney donors) were included. The literature retrieval, review, and selection process are demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, living donor KTx provides greater allograft longevity than those transplanted from a deceased donor [ 57 ]. However, changes in serum klotho levels and the impact of klotho on outcomes among KTx recipients and kidney donors remain unclear [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Thus, we conducted this systematic review and meta-analysis to assess serum klotho levels and the impact of klotho on outcomes among KTx recipients and kidney donors…”
Section: Introductionmentioning
confidence: 99%
“…The authors proposed that Klotho was mediating the rapamycin-related clinical alterations. In a renal transplantation clinical trial, everolimus significantly increased Klotho serum levels ( Mizusaki et al, 2019 ). These investigators measured Klotho levels before transplantation and 1 year after.…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%
“…Statins: Adeli et al, 2017 ; Janic et al, 2019 ; Kuwahara et al, 2008 ; Narumiya et al, 2004 ; Yoon et al, 2012 . PPAR-γ agonists: Chen LJ, et al, 2014 ; Cheng et al, 2017 ; Huang KC, et al, 2014 ; Maquigussa et al, 2018 ; Shen et al, 2018 ; Zhang H, et al, 2008. mTOR inhibitors: Mizusaki et al, 2019 ; Tabibzadeh, 2021 ; Tataranni et al, 2011 ; Zhao Y, et al, 2015. Vitamin D: Haussler et al, 2020 ; Kuro-o, 2019 ; Lerch et al, 2018 ; Tsujikawa al., 2003.…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%
“…Finally, Klotho can be inducible by other substances and then acts as an induced protective factor to inhibit VC. Upregulation of Klotho expression by inhibiting mTOR signaling via oral rapamycin ameliorates VC and protects against vascular disease in CKD [60]. Another study showed that intermedin 1-53 attenuates VC in rats with CKD by upregulating membrane-bound Klotho expression in the vessel wall [61].…”
Section: The Role Of Klotho In Vcmentioning
confidence: 99%